PELATIHAN HIDROPONIK UNTUK MENINGKATKAN KETERAMPILAN GURU-GURU PAUD - Ni Wayan Suardiati Putri; Kadek Suryati; Ketut Sepdyana Kartini; Ni Wayan Eka Wijayanti; I Wayan Gede Wardika; Evi Dwi Krisna (PUAN INDONESIA, 2022)
From the results of discussions conducted with the Principal of the Kindergarten School. Kartika, it was agreed that the problems that were resolved in this activity were: 1) So that Partners had fun gardening media; 2) So that Partners have knowledge and skills in managing hydroponic gardens. The agreed solutions to solve the problems faced by Partners are as follows: 1) Procurement of hydroponic gardening equipment, so that gardening becomes cleaner and more attractive; 2) Training on hydroponic gardening procedures for teachers. The results of the activity showed that there was an increase in teachers' understanding of hydroponic farming by 90%. Besides that, there is also an increase in teacher skills in hydroponic farming as shown by good plant growth during the harvest period.